2018
DOI: 10.5455/jtomc.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy indications and postoperative follow-up results of a department of general surgery

Abstract: Aim: Splenectomy is commonly performed in many centers around the world for the treatment of various benign, malign diseases and trauma nowadays. The purpose of this study is to determine the indications in patients undergoing splenectomy in a general surgery department for five years and to investigate the mortality rate and reasons. Material and Methods: Data of the study were obtained retrospectively by scanning records of patients over the age of 18 who underwent open splenectomy in the general surgery dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Consistently Mehboob A et al [14] reported that the most of the cases 56%, were found with age group of 21-40 years and in the line of this study, they found males in majority 93% and only 7% were females. On other hand Emre A et al [10] demonstrated that the patient's international study may because in our societies males are mostly involved in outdoor activities, therefore they are on high risk on these types' traumas [15].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Consistently Mehboob A et al [14] reported that the most of the cases 56%, were found with age group of 21-40 years and in the line of this study, they found males in majority 93% and only 7% were females. On other hand Emre A et al [10] demonstrated that the patient's international study may because in our societies males are mostly involved in outdoor activities, therefore they are on high risk on these types' traumas [15].…”
Section: Discussionmentioning
confidence: 95%
“…In this study the morbidity occurred in 30 patients (50.0%), 10 (16.7%) cases of pulmonary infection, Intra-abdominal bleeding was seen in 08(13.3%) cases, wound infection was present in 9(15.0%) and one (1.6%) developed overwhelming post splenectomy (OPSS). The most prevalent post-splenectomy consequences are lower lobe atelectasis and pneumonia, in addition, hemorrhages due to insufficient local hemostasis, infective complications from a wound infection, subphrenic abscess, and encapsulated bacteria, pseudocyst and fistula formation due to traumatic injuries of the pancreas during the dissection of the splenic hilus and coagulation abnormalities from hematological variations could occur in individuals [10,17,18]. Consistently Gangat SA et al [17] demonstrated that the 15.9% pulmonary infection, 11.3% septicemia, 6.8% pancreatic fistula, 2.2% subphrenic abscess, 13.6% wound infection and 2.2% pneumococcal pneumonia were post operative complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations